2001
DOI: 10.1076/edre.7.2.185.3869
|View full text |Cite
|
Sign up to set email alerts
|

Technology Integration for Students with Disabilities: Empirically Based Recommendations for Faculty

Abstract: In 3 empirical studies we examined the computer technology needs and concerns of close to 800 college and university students with various disabilities. Findings indicate that the overwhelming majority of these students used computers, but that almost half needed some type of adaptation to use computers effectively. Data provided by the students and by a small sample of professors underscore the importance of universal design in a variety of areas: courseware development, electronic teaching and learning mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, the area of assistive technology most needed by students with disabilities was a desktop computer and again a personal notebook. This result relates to studies by Fichten et al [18] and Goodman et al [19], who found that students with disabilities frequently used computers and the internet in their daily lives and for educational purposes. Moreover, the findings of this study are consistent with results from Gitlow et al [20], who stated that the needs identified most frequently existed in the categories of aids for hearing and vision.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, the area of assistive technology most needed by students with disabilities was a desktop computer and again a personal notebook. This result relates to studies by Fichten et al [18] and Goodman et al [19], who found that students with disabilities frequently used computers and the internet in their daily lives and for educational purposes. Moreover, the findings of this study are consistent with results from Gitlow et al [20], who stated that the needs identified most frequently existed in the categories of aids for hearing and vision.…”
Section: Discussionmentioning
confidence: 66%
“…In order for education to be accessible to students with disabilities, several factors should be addressed, including the provision of services, the awareness of using assistive technology, and the support in the form of available assistive devices and educational services from university administration [22]. Additionally, most students need access to information and adaptations, such as screen magnification, dictation software, Braille, and screen readers, in order to use computers effectively [18]. These results can reflect the actions of students with disabilities, who are the stakeholders in assistive technology.…”
Section: Discussionmentioning
confidence: 99%
“…One of the eight survey studies reported the experiences of university students with disabilities using augmentative and alternative communication (Atanasoff, McNaughton, Wolfe, & Light, 1998) and found that e-mail communication was more effective than face-to-face or other written forms of communication. Fichten and colleagues (2000;2001) reported on the accessibility of computers for postsecondary students with disabilities in two articles; the studies included focus groups (n = 12), interviews (n = 37), and surveys (n = 725). Twenty-three of the interviewed students and 358 of the surveyed students reported a physical disability.…”
Section: Research Methods Usedmentioning
confidence: 99%
“…Online learning may also allow students with a disability to choose whether to reveal their disability at their discretion, while promoting equity and reducing discrimination (Fichten et al 2009, p. 242;McFarland and Fuller 2001). However, online learning may also exclude students with a disability if it is not thoughtfully designed to be mindful of their accessibility needs (Fichten et al 2000(Fichten et al , 2001McFarland and Fuller 2001). For example, use of online learning can pose problems for students with learning, visual and neuromuscular disabilities if it impairs their ability to use adaptive software capable of screen magnification, screen reading and dictation (Burgstahler, Corrigan, and McCarter 2004, p. 234;Seale andCooper 2010, p. 1108).…”
Section: Disabilitymentioning
confidence: 99%